Association Of Sclerodema With Pelvic Floor Muscle Dysfunction - A Case Report (Journal of Pharmaceutical Negative Results, 2022)
Scleroderma is a rare multisystemic autoimmune disease characterised by vasculopathy, inflammation and fibrosis of the skin and many other organs. Here we report a case of a 56 year old female who presented with Limited cutaneous scleroderma associated with pelvic floor dysfunction with uterine, rectal and bladder prolapse, recurrent hernias, urinary incontinence and bilateral varicose veins. These associations have been reported in literature but overlooked as an association or manifestation of scleroderma due to its uncommon presentation along with the disease. All these associations should be kept in mind and screened for in all patients presenting with Scleroderma for better management of overall condition of the patient and to also address female sexual dysfunction , thus helping in improving the quality of life of these patients.